2014
DOI: 10.1371/journal.pone.0103369
|View full text |Cite
|
Sign up to set email alerts
|

Violations of Personal Space by Individuals with Autism Spectrum Disorder

Abstract: The ability to maintain an appropriate physical distance (i.e., interpersonal distance) from others is a critical aspect of social interaction and contributes importantly to real-life social functioning. In Study 1, using parent-report data that had been acquired on a large number of individuals (ages 4–18 years) for the Autism Genetic Resource Exchange and the Simons Simplex Collection, we found that those with Autism Spectrum Disorder (ASD; n = 766) more often violated the space of others compared to their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
66
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 25 publications
8
66
3
Order By: Relevance
“…In stark contrast to the findings of Gessaroli and colleagues (2013), Kennedy and Adolphs (2014) found that individuals with ASD were more likely to be reported by parents to violate the personal space of others. Indeed, 79% of parents report that their children with ASD have smaller personal space boundaries compared to their TD siblings.…”
contrasting
confidence: 98%
See 4 more Smart Citations
“…In stark contrast to the findings of Gessaroli and colleagues (2013), Kennedy and Adolphs (2014) found that individuals with ASD were more likely to be reported by parents to violate the personal space of others. Indeed, 79% of parents report that their children with ASD have smaller personal space boundaries compared to their TD siblings.…”
contrasting
confidence: 98%
“…There are several items relating to personal space that have been examined in the work of Kennedy and Adolphs (2014) and Lough and colleagues (2015a) and are therefore of interest to the current study. They examined item 55 which asks parents to rate the following statement: "knows when he or she is too close to someone or is invading someone's space".…”
Section: Social Responsiveness Scalementioning
confidence: 99%
See 3 more Smart Citations